Catalytic properties of xylanases produced by Trichoderma piluliferum and Trichoderma viride and their application as additives in bovine feeding. (May 2019) - Costa, Ana Carolina da; Cavalheiro, Gabriéla Finoto; Vieira, Elis Regina de Queiroz; Gandra, Jefferson Rodrigues; Goes, Rafael Henrique de Tonissi e Buschinelli de; Paz, Marcelo Fossa da; Fonseca, Gustavo Graciano; Leite, Rodrigo Simões Ribeiro
Abstract: This study investigated the xylanases produced by Trichoderma piluliferum and T. viride . These enzymes were characterized and used as additives in bovine diet. The fungus T. piluliferum was a more efficient producer of xylanase (301 U g −1 dry substrate) when grown on wheat bran, with 75 or 80% moisture for 96 h. The optimum pH of the enzyme produced by T. piluliferum was 4.5, obtaining as the optimum temperature 50 °C. The enzyme was stable at a wide pH range (3.0–10.0), and it remained stable for 1 h at 40 °C. The best culture parameters for the cultivation of T. viride (671 U g −1 dry substrate) were as follows: wheat bran as substrate, 65, 70 and 75% initial moisture, and 48 h cultivation time. The optimum pH and temperature for the xylanase produced by this fungus were 6.0 and 45 °C, respectively, and the enzyme was stable at a wide pH range (3.0–10.0), maintaining its activity after 1 h at 40 °C. Both the enzyme extracts produced were effective at increasing digestibility of Tifton 185 hay, sugarcane silage, and corn silage. The enzymatic extracts proved promising for xylooligosaccharides production and showed low cellulase activity, indicating potential for application in biobleaching processes of cellulose pulp and paper. Highlights: Xylanases production by Trichoderma piluliferum and Trichoderma viride . Catalytic properties of the enzymatic extracts. Catalytic profile of the xylanases by thin layer chromatography (TLC). Application of the enzymatic extracts as additives in bovine diet.